Análise bioquímica e molecular da diversidade genética entre cultivares mesoamericanos e andinos de feijoeiro comum (Phaseolus vulgaris L.) - Belele, Christiane Luiza (1997)
Common bean (Phaseolus vulgaris L.) is characterized by extensive genetic variability. Biochemical, physiological and morphological evidence suggests that this variability is not randomly distributed among genotypes, but is associated with two distinct centers of diversity, known as Mesoamerican and Andean gene pools (Gepts et al, 1986). The cultivars belonging to each of these gene pools have been subdivided into 12 gene pools (Singh et al., 1989 cited by Singh, 1991) or 6 races (Singn et al., 1901c ')) by morphological, agronomic and However, some of the morphological characters considered in the divisions of the Mesoamerican and Andean cultivars are quantitative in nature and are therefore subject to complex genetic control and great environmental influence, making them unsuitable for a correct assessment of genetic diversity. In view of these aspects, the objective of this study is to re-evaluate the distribution of genetic diversity in molecular and biochemical susceptible cells by means of RAPD and SenDeo-praGF electrophoresis techniques of phaseolin, albumin and soluble protein fractions in NaCl e0x 5is tmMc. iaA d ea vnaárliiaseb ildidoasd ep daedsrtõess p aedfreôtreosf eonrétrtiec ooss cdueltsitvaasr elsr aaçvõaleisa dposro. tEéisctaa sv amriaobsitlriodua dea did not occur randomly between cultivars and allowed them to be separated into two distinct groups according to their center of origin.